A New Method for C−H Functionalization of Aliphatic Compounds by an Unusual Photochemical Reaction of Diazoketones without Elimination of Nitrogen. Issue 5 (29th March 2016) - Rodina, Liudmila L.; Galkina, Olesia S.; Maas, Gerhard; Platz, Matthew S.; Nikolaev, Valerij A.
Abstract: Benzophenone‐sensitized reactions of 4‐diazotetrahydrofuran‐3(2 H )‐ones with H‐donors such as tetrahydrofuran, 1, 4‐dioxane, cyclohexane and diethyl ether, occur without elimination of nitrogen and give rise to the corresponding N‐substituted hydrazones or bis‐hydrazonoethanes due to a formal insertion of the terminal N atom of diazo group into α‐C−H bonds of ethers and aliphatic hydrocarbons, with yields of up to 78 %. Long‐wavelength UV irradiation ( λ >310 nm) is most suitable for this process, whereas oxygen molecules adequately quench the triplet excited state of the diazoketone and reduce the preparative yields of C−H‐insertion products. Hence this photochemical reaction of diazoketones can be used for C−H functionalization of different aliphatic compounds. Abstract : Insert here : Benzophenone‐sensitized reactions of 4‐diazotetrahydrofuranones with H‐donors, unlike direct irradiation processes, occur without elimination of nitrogen and give rise to the corresponding N‐substituted hydrazones or bis‐hydrazonoethanes with yields of up to 78 %.